PENERAPAN PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS XI IPA.2 SMAN 6 PEKANBARU - Lasma Br Hotang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
This research aimed to improve the ability of the phisic subject XI IPA2 SMAN 6 Pekanbaru students. Students were not encouraged to develop critical thinking skills where the results obtained are only 8 out of 32 (24%) students who complete while the other 25 (76%) students have not yet reached KKM (Minimum Completeness Criteria). The research method used was the Classrom Action Research (CAR) which consist of 2 cycles. Before the treatment was performed, the students were given a pre-test, and after the treatment a post-test was administered. The research findings The average daily test scores were 68.33 enough categories and in the second cycle the number of students whose grades were complete were 30 people (91%) with